Aggregation-induced electrochemical luminescence composite material and application thereof in folic acid detection
By introducing Cu NCs into PAA hydrogel to prepare Cu NCs@PAA hydrogel composites, aggregation-induced electrochemiluminescence sensors are constructed, which solves the problem of time-consuming and labor-intensive and low sensitivity of existing folic acid detection methods, and achieves high sensitivity and high selectivity folic acid detection.
Patent Information
- Application Number
- CN202510107366.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-25
AI Technical Summary
The existing folic acid detection methods have problems such as time-consuming, complex operation, long detection time, high background signal, low sensitivity and narrow dynamic range, which limits its practical application.
Cu NCs@PAA hydrogel composites were prepared by introducing copper nanoclusters (Cu NCs) into polyacrylic acid (PAA) hydrogels, and an aggregation-induced electrochemiluminescence sensor was constructed based on this system for high sensitivity and high selectivity detection of folic acid.
It realizes ultra-sensitive detection of folic acid, has high sensitivity, low detection limit, good stability and reproducibility, overcomes the shortcomings of traditional methods, and provides a reliable and convenient detection method.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of biochemical analysis and nanomaterial technology, and specifically relates to an aggregation-induced electrochemiluminescent composite material and its application in folic acid detection, and particularly relates to a method for constructing an electrochemiluminescent sensor based on PAA hydrogel for aggregation-induced Cu NCs and its application in folic acid detection. Background Art
[0002] Folic acid (FA) plays a key role in human physiology. It can prevent fetal neural tube defects, ensure fetal development, and reduce the risk of anemia in pregnant women. It can reduce the risk of stroke, prevent Alzheimer's disease, improve memory, and reduce the risk of chronic diseases in middle-aged and elderly people. However, the human body cannot synthesize folic acid and needs to obtain it from food or supplements. Deficiency or excess can cause health problems. Therefore, it is crucial to develop sensitive and reliable folic acid detection technology. Currently, there are various methods for folic acid detection. Although traditional electrochemical analysis, fluorescence analysis, chemiluminescence determination, and liquid chromatography analysis have their own characteristics, they generally have shortcomings. Most of these methods are time-consuming and labor-intensive, with complex operation procedures and long detection time. The high background signal affects the accuracy and sensitivity. The narrow dynamic range makes it difficult to meet the detection requirements of different concentrations, which limits practical applications. Compared with these methods, the emerging electrochemiluminescence (ECL) has been widely used in bioanalysis in recent years. ECL has the advantages of excellent controllability, simple equipment, simple optical settings, near zero background, and high sensitivity.
[0003] Electrochemiluminescence (ECL) technology is emerging and has great potential. Its advantages such as low background, high sensitivity and simple operation show great application potential in the field of bioanalysis. However, traditional organic luminescent materials have the problem of aggregation quenching (ACQ effect) due to high molecular density, which limits the development of ECL. Although there is the concept of aggregation-induced electrochemiluminescence (AIECL), the existing AIECL materials face the difficulties of poor film formation, cumbersome synthesis, harsh conditions and high cost of rare precious metals, which hinder their widespread application and breakthrough. Therefore, it is a worthy research topic to find new AIECL emitters with high AIECL performance, simple synthesis method, low toxicity, good film formation and reduced ACQ phenomenon. In recent years, the research on AIECL of metal nanoclusters (such as Au NCs, Ag NCs and CuNCs) has also been reported. Among them, copper nanoclusters (Cu NCs) have low preparation cost, good optical properties and good biocompatibility, and have application prospects in many fields. It is very suitable as an AIE material, but Cu NCs have poor stability and are prone to agglomeration or oxidation, and their ECL emission is weak, which limits their application in high-sensitivity detection.
[0004] As we all know, polyacrylic acid (PAA) is a known hydrogel with excellent properties such as high water solubility, weather resistance, non-toxicity, biodegradability and biocompatibility. The three-dimensional structure of PAA hydrogel can lead to a "cage effect", which provides a stable environment for metal nanoclusters. + It is a suitable cross-linker for forming PAA networks. PAA functionalized hydrogels also have good conductivity and biocompatibility, and can be restricted by templates to enhance fluorescence, thereby producing strong AIE.
[0005] In this invention, Cu NCs were introduced into PAA hydrogel with constrained volume to prepare a novel functional Cu NCs@PAA hydrogel composite with excellent AIECL performance. Based on the Cu NCs@PAA hydrogel system, a novel biosensor for the detection of folic acid (FA) in human serum and actual medicines was established. The designed ECL sensor has high sensitivity and good stability. In addition, this work will provide a solid foundation for the further application of AIECL between Cu NCs. Summary of the invention
[0006] In view of the above problems existing in the prior art, the present invention aims to provide a method for constructing an electrochemiluminescence sensor based on PAA hydrogel for aggregation-induced Cu NCs, so as to achieve ultra-sensitive and highly selective detection of folic acid, while overcoming many deficiencies of existing detection technologies and materials, and providing a reliable and convenient detection method for biomedical research and clinical diagnosis.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: In the first aspect, the present invention provides an aggregation-induced electrochemiluminescent composite material, wherein the composite material is copper nanoclusters (Cu NCs) confined in a three-dimensional structure of polyacrylic acid (PAA) hydrogel, wherein the PAA hydrogel is acrylic acid in the presence of an initiator and Ag. + The hydrogel formed under the action of the cross-linking agent, and the composite material is represented as Cu NCs@PAA hydrogel composite material.
[0008] Furthermore, the ratio of Cu NCs to acrylic acid is 0.1-0.5 mol:30 L, preferably 0.2-0.4 mol:30 L, and more preferably 0.3 mol:30 L. The initiator is ammonium persulfate.
[0009] In a second aspect, the present invention provides a method for preparing the above-mentioned Cu NCs@PAA hydrogel composite material, comprising the following steps: Step a, preparation of PAA hydrogel template: accurately measure silver nitrate solution, freshly prepared ammonium persulfate solution and acrylic acid, and fully disperse them in ultrapure water; at room temperature, after 3 to 7 minutes of rapid reaction, ultra-fast gelation can be achieved to obtain elastic and viscous PAA hydrogel; wherein the volume ratio of silver nitrate solution, ammonium persulfate solution, acrylic acid and ultrapure water is 7:10:12:23.
[0010] Step b, using the PAA hydrogel synthesized as above as a template, generating copper nanoclusters on the basis of the PAA hydrogel; adding copper sulfate solution to the PAA hydrogel and mixing thoroughly; adjusting the pH value of the system to alkaline using sodium hydroxide solution; during this process, it can be observed that the color of the solution gradually changes from colorless to light blue; after the solution is thoroughly mixed, carefully adding hydrazine hydrate solution; with the addition of hydrazine hydrate, the color of the solution will further change from light blue to dark brown, and this color change indicates that Cu NCs@PAA is successfully prepared.
[0011] In some embodiments, in step a, the concentration of the silver nitrate solution is 5 to 15 mmol L ‒1 , preferably 10 mmol L ‒1 The concentration of ammonium persulfate solution is 30~70mmol L ‒1 , preferably 50 mmol L ‒1 The gelation time of PAA hydrogel is 3 to 7 minutes.
[0012] In some embodiments, in step b, the concentration of the copper sulfate solution is 5 to 15 mmol L ‒1 , preferably 8 mmol L ‒1 , the volume ratio of copper sulfate solution to acrylic acid is 5~25:12.
[0013] In some examples, in step b, the pH is preferably adjusted to 12.
[0014] In a third aspect, the present invention provides an aggregation-induced electrochemiluminescence biosensor, comprising a modified electrode obtained by modifying the Cu NCs@PAA hydrogel composite material on the surface of a conductive substrate.
[0015] In some examples, the prepared Cu NCs@PAA hydrogel is modified onto the surface of a glassy carbon electrode, and after drying, Cu NCs@PAA / GCE is obtained.
[0016] In a fourth aspect, the present invention also provides application of the above biosensor in folic acid detection.
[0017] Specifically, the electrode modified with Cu NCs@PAA hydrogel composite material (Cu NCs@PAA / GCE) was used as the working electrode, the platinum wire electrode was used as the counter electrode, and the silver / silver chloride electrode was used as the reference electrode. Based on the three-electrode detection system, its ECL performance was tested in a phosphate buffer solution containing 80-120 mM K2S2O8 and pH 7.4; the scanning potential range applied in the experiment was -2 to 0 V, the photomultiplier tube high voltage was 800 V, and the scanning rate was 100 mV / s. Folic acid has a significant quenching effect on the ECL signal probe of Cu NCs@PAA. This is because folic acid can be quenched by SO4 •− (an intermediate of K2S2O8) preferentially oxidizes FA to 2-amino-1,4-dihydro-4-oxopyrimidine-6-carboxylic acid (ADOCA), which leads to SO4 •− The free radicals are consumed, and SO4 reacts with Cu NCs@PAA •− The electrochemiluminescence signal of Cu NCs@PAA will decrease, and the corresponding electrochemiluminescence signal of Cu NCs@PAA will decrease, resulting in the signal shutdown detection of FA. By measuring different concentrations of FA under continuous potential scanning, a stable ECL-time curve is obtained, and a linear relationship curve is drawn according to the ECL test results; the ECL intensity of folic acid in the sample is detected, and the concentration of folic acid in the sample is calculated according to the obtained linear relationship curve.
[0018] The biosensor constructed by the present invention can be used not only for actual analysis of human serum but also for actual drug detection.
[0019] In some instances, the applicable detection range of the constructed biosensor is 100pM to 50μM, and it has efficient analytical detection capabilities; based on the signal test results of various interfering substances, it is shown that the constructed biosensor has high specificity; based on the results of multiple cycle tests, the constructed biosensor has good stability; based on the signal responses of different batches of biosensors, the constructed biosensor has good reproducibility.
[0020] Compared with the prior art, the present invention has at least one of the following beneficial effects: The present invention successfully synthesized a Cu NCs@PAA hydrogel composite material. Due to the restriction effect of the PAA hydrogel on Cu NCs, the composite material exhibited obvious aggregation and obvious lattice structure. The ECL emission of the Cu NCs@PAA provided by the present invention originated from the surface state rather than the emission driven by the band gap. The introduction of the PAA hydrogel can significantly enhance the ECL intensity of the Cu NCs. The composite material has excellent aggregation-induced electrochemiluminescence performance.
[0021] The preparation method of the invention is simple and easy to implement. When the prepared composite material is used for detecting folic acid, it has high sensitivity and low detection limit, good stability and reproducibility, excellent selectivity and relatively broad practical application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The present invention is further described below in conjunction with the accompanying drawings.
[0023] Figure 1 This is the transmission electron microscopy of the Cu NCs (A) and Cu NCs@PAA (B, C) composite materials prepared in Example 1.
[0024] Figure 2 This is the X-ray photoelectron spectrum of the Cu NCs@PAA composite material prepared in Example 1.
[0025] Figure 3 The UV-visible absorption spectra of the Cu NCs@PAA composite material, Cu NCs and PAA hydrogel prepared in Example 1.
[0026] Figure 4 The fluorescence spectrum and electrochemiluminescence spectrum of the Cu NCs@PAA composite material prepared in Example 1.
[0027] Figure 5 The Cu NCs@PAA composite material, GCE, S2O8 prepared in Example 1 2- , ECL-time diagram (A) and cyclic voltammogram (B) of Cu NCs.
[0028] Figure 6 This is the stability diagram of the Cu NCs@PAA composite material prepared in Example 1.
[0029] Figure 7 ECL-time curve (A) and corresponding linear equation (B) of the sensor constructed with the Cu NCs@PAA composite material prepared in Example 1.
[0030] Figure 8 Selectivity (A) and reproducibility (B) of the sensor constructed with the Cu NCs@PAA composite material prepared in Example 1.
[0031] Fig. 9 This is the stability diagram of the Cu NCs@PAA composite material prepared in Example 2.
[0032] Fig.10 This is the stability diagram of the Cu NCs@PAA composite material prepared in Example 3.
[0033] Fig.11This is the stability diagram of the Cu NCs@PAA composite material prepared in Example 4.
[0034] Fig.12 This is the stability diagram of the Cu NCs@PAA composite material prepared in Example 5.
[0035] Fig.13 This is the stability diagram of Cu NCs prepared in Comparative Example 1.
[0036] Fig.14 This is the stability diagram of the Ag NCs@PAA composite material prepared in Comparative Example 2. DETAILED DESCRIPTION
[0037] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but the present invention is not limited to the following embodiments. Embodiment 1
[0038] An electrochemiluminescent sensor based on PAA hydrogel for inducing aggregation of Cu NCs and a preparation method thereof, comprising the following steps: (1) Take 70 μL of AgNO3 (10 mmol L ‒1 ), 100 μL of freshly prepared ammonium persulfate (50 mmol L ‒1 ) and 120 μL of acrylic acid dispersed in 230 μL of ultrapure water can achieve ultra-fast gelation. Then, using PAA hydrogel as a template, copper nanoclusters were generated on it. First, 150 μL of CuSO4 (8 mmol L ‒1 ) solution, and after it is fully mixed, NaOH solution is added to adjust the pH to 12. At this time, the color of the solution gradually changes from colorless to light blue. After the solution is fully mixed, 100 μL of hydrazine hydrate solution is finally added. At this time, the color of the solution changes from light blue to dark brown, indicating that the Cu NCs@PAA hydrogel composite material is successfully prepared.
[0039] (2) The Cu NCs@PAA hydrogel composite material obtained in step (1) is coated on the polished electrode surface, and after drying, an ECL intensity test is performed on it using an electroluminescence instrument.
[0040] Figure 1 (A), (B), and (C) are transmission electron micrographs of Cu NCs and Cu NCs@PAA hydrogel composites, respectively. Figure 1 (A) It can be seen that the Cu NCs synthesized in the water sample are regular spherical and have good dispersion. Figure 1As can be seen from (B, C), the Cu NCs@PAA hydrogel composites exhibit obvious aggregation and a distinct lattice structure, which is mainly due to the confinement effect of PAA hydrogel on Cu NCs.
[0041] Figure 2 This is the X-ray photoelectron spectrum of Cu NCs@PAA hydrogel composite material, which further confirms the correlation between the element type and valence state of Cu NCs in the PAA hydrogel composite material. Figure 2 (A) is the overall spectrum of Cu NCs@PAA hydrogel composites. Figure 2 In (B), the XPS spectrum of Ag 3d has two prominent orbital peaks, which are attributed to 3d 3 / 2 and 3D 5 / 2 The peak separation process yielded four characteristic peaks, of which the characteristic peaks at 373.4eV and 367.6eV were attributed to Ag. 0 , the characteristic peaks at 373.9eV and 368.8eV are attributed to Ag + .exist Figure 2 In (C), the Cu 2p region has an obvious characteristic peak at 932.3 eV, which belongs to the Cu 2p of Cu(0) and Cu(I). 3 / 2 , and there is no characteristic peak of Cu 2p around 942eV, indicating that there is no Cu (II) in the Cu NCs@PAA hydrogel composite, proving the successful synthesis of Cu NCs. Therefore, in the Cu NCs@PAA hydrogel composite, the valence state of Cu may be between 0 and +1. These results also prove the successful synthesis of the Cu NCs@PAA hydrogel composite.
[0042] Figure 3 The UV-visible absorption spectrum of Cu NCs@PAA hydrogel composite material is shown in Figure 2. It can be observed that the characteristic absorption peak of Cu nanoparticles at 500-600nm is not observed in the UV-visible spectra of Cu NCs and Cu NCs@PAA, which indirectly confirms the successful synthesis of nanoclusters. Cu NCs@PAA shows a strong characteristic absorption peak in the UV-visible spectrum around 417nm, which may be due to the interaction between some carboxyl groups in the PAA structure and Ag. + The coordination reaction and self-assembly process form silver nanostructures.
[0043] Figure 4The fluorescence emission spectrum and electrochemiluminescence spectrum of the Cu NCs@PAA hydrogel composite material can be seen from the figure. Under the 470nm excitation light, the fluorescence emission light can be clearly observed at 514nm, while the ECL emission wavelength is located at 525nm. It is not difficult to notice that compared with the fluorescence emission spectrum, the electrochemiluminescence spectrum has a red shift of 11nm. This red shift is caused by the different excited states between electrochemiluminescence emission and fluorescence emission, indicating that the ECL emission of Cu NCs@PAA originates from the surface state rather than the band gap driven emission.
[0044] Figure 5 Cu NCs and Cu NCs@PAA hydrogel composites at 100 mmol L -1 ECL intensity and corresponding CV curve measured in K2S2O8. Figure 5 As can be seen from Figures 5(A) and 5(B), when bare GCE was subjected to ECL measurement in buffer PBS, no obvious ECL was observed (Figure A, a), and no obvious redox peak was observed in the corresponding CV detection (Figure B, a), indicating that PBS has no obvious ECL behavior in the potential range of -2 to 0 V. -1 When the K2S2O8 solution was tested, a weak ECL signal was observed (Figure A, b), and a corresponding reduction peak was observed at around -1 V in the corresponding CV test (Figure B, b), indicating that K2S2O8 has a weak ECL behavior in the potential range of -2 to 0 V. -1 When tested in K2S2O8 solution, a weak ECL response (about 1554 a.u.) appeared (Figure A, c), and the corresponding CV test showed a new reduction peak at -1.39 V, indicating that S2O8 2- Can act as a coreacting agent to react with the free radicals generated by the reduction of Cu NCs (Cu NCs •− ) reaction, generating ECL signals. When Cu NCs@PAA hydrogel composite modified GCE (Cu NCs@PAA / GCE) was exposed to 100 mmol L -1 When tested in K2S2O8 solution, an obvious ECL response (about 6755 a.u.) appeared (Figure A, d). Compared with Cu NCs / GCE, its ECL signal increased by about 4.3 times. At the same time, the corresponding CV curve also showed that its reduction peak position moved in the negative direction and the reduction current increased, indicating that the introduction of PAA hydrogel can significantly enhance the ECL intensity of Cu NCs.
[0045] Figure 6Cu NCs@PAA hydrogel composites at 100 mmol L -1 The ECL stability graph of 10 consecutive scans in K2S2O8 solution shows that the prepared composite material exhibits excellent stability, and its relative standard deviation (RSD) is 1.9%.
[0046] Figure 7 A new biosensor for detecting folic acid (FA) was established based on the Cu NCs@PAA hydrogel system and its performance was tested. Folic acid solutions were uniformly dispersed in 0.1M phosphate buffer solution with a pH of 7.4 at concentrations of 0.05μM, 0.1μM, 0.5μM, 1μM, 5μM, 10μM, 50μM, and 100μM to obtain folic acid solutions of different concentrations. Under 3 consecutive cycles of potential scanning, the constructed sensor can obtain stable ECL-time curves when measuring different concentrations of FA, indicating that the constructed sensor has good stability. And from Figure (A), it can be clearly seen that the ECL signal of Cu NCs@PAA decreases with the increasing concentration of FA, indicating that FA has a significant quenching effect on the ECL signal probe of Cu NCs@PAA. This is because folic acid can be absorbed by SO4 •− Oxidation to ADOCA, which leads to SO4 •− The free radicals were consumed, and at a FA concentration of 5.0×10 -2 ~1.0×10 2 μmol L -1 Within the range, ( I 0- I ) / I There is a good linear relationship between the 0 value and the logarithmic value of FA concentration, as shown in Figure (B), and the related linear equation is: (I 0 -I) / I 0 = 0.2364 lg C FA + 0.3662 (R 2 =0.9956)(where, I 0 is a blank ECL signal. I is the ECL signal value measured under different FA concentrations, C is the FA concentration). The related detection limit (LOD) was calculated to be 1.8×10 -2 μmol L -1 .
[0047] Figure 8To investigate the selectivity and reproducibility of the constructed Cu NCs@PAA sensor, we selected several interferents such as uric acid (UA), ascorbic acid (AA), glucose (Glu), glutathione (GSH), bovine serum albumin (BSA), potassium chloride (KCl) and zinc sulfate (ZnSO4) to evaluate the selectivity of the sensor. Figure 8 As shown in (A), the ECL signal changes caused by these interferents are negligible compared to FA, indicating that only FA can quench the ECL signal of Cu NCs@PAA. The above results show that the constructed ECL sensor has good selectivity. Finally, the reproducibility of the sensor was evaluated. Figure 8 As shown in (B), when the Cu NCs@PAA composite material was modified on 7 different electrodes and FA was detected, a relatively stable ECL intensity was observed, with a relative standard deviation (RSD) of 2.8%, indicating that the constructed sensor has good reproducibility. Embodiment 2
[0048] An electrochemiluminescent sensor based on PAA hydrogel for inducing aggregation of Cu NCs and a preparation method thereof, comprising the following steps: (1) Take 70 μL of AgNO3 (10 mmol L ‒1 ), 100 μL of freshly prepared ammonium persulfate (50 mmol L ‒1 ) and 120 μL of acrylic acid dispersed in 230 μL of ultrapure water can achieve ultra-fast gelation. Then, using PAA hydrogel as a template, copper nanoclusters were generated on it. First, 50 μL of CuSO4 (8 mmol L ‒1 ) solution, and after it is fully mixed, NaOH solution is added to adjust the pH to 12. At this time, the color of the solution gradually changes from colorless to light blue. After the solution is fully mixed, 100 μL of hydrazine hydrate solution is finally added. At this time, the color of the solution changes from light blue to dark brown, indicating that the Cu NCs@PAA hydrogel composite material is successfully prepared.
[0049] (2) The Cu NCs@PAA hydrogel composite material obtained in step (1) is coated on the polished electrode surface, and after drying, an ECL intensity test is performed on it using an electroluminescence instrument.
[0050] Fig. 9 Cu NCs@PAA hydrogel composites at 100 mmol L -1 The ECL stability graph of 10 consecutive scans in K2S2O8 solution shows that the prepared composite material exhibits excellent stability, and its relative standard deviation (RSD) is 2.0%. Embodiment 3
[0051] An electrochemiluminescent sensor based on PAA hydrogel for inducing aggregation of Cu NCs and a preparation method thereof, comprising the following steps: (1) Take 70 μL of AgNO3 (10 mmol L ‒1 ), 100 μL of freshly prepared ammonium persulfate (50 mmol L ‒1 ) and 120 μL of acrylic acid dispersed in 230 μL of ultrapure water can achieve ultra-fast gelation. Then, using PAA hydrogel as a template, copper nanoclusters were generated on it. First, 100 μL of CuSO4 (8 mmol L ‒1 ) solution, and after it is fully mixed, NaOH solution is added to adjust the pH to 12. At this time, the color of the solution gradually changes from colorless to light blue. After the solution is fully mixed, 100 μL of hydrazine hydrate solution is finally added. At this time, the color of the solution changes from light blue to dark brown, indicating that the Cu NCs@PAA hydrogel composite material is successfully prepared.
[0052] (2) The Cu NCs@PAA hydrogel composite material obtained in step (1) is coated on the polished electrode surface, and after drying, an ECL intensity test is performed on it using an electroluminescence instrument.
[0053] Fig.10 Cu NCs@PAA hydrogel composites at 100 mmol L -1 The ECL stability graph of 10 consecutive scans in K2S2O8 solution shows that the prepared composite material exhibits excellent stability, and its relative standard deviation (RSD) is 4.0%. Embodiment 4
[0054] An electrochemiluminescent sensor based on PAA hydrogel for inducing aggregation of Cu NCs and a preparation method thereof, comprising the following steps: (1) Take 70 μL of AgNO3 (10 mmol L ‒1 ), 100 μL of freshly prepared ammonium persulfate (50 mmol L ‒1 ) and 120 μL of acrylic acid dispersed in 230 μL of ultrapure water can achieve ultra-fast gelation. Then, using PAA hydrogel as a template, copper nanoclusters were generated on it. First, 200 μL of CuSO4 (8 mmol L ‒1) solution, and after it is fully mixed, NaOH solution is added to adjust the pH to 12. At this time, the color of the solution gradually changes from colorless to light blue. After the solution is fully mixed, 100 μL of hydrazine hydrate solution is finally added. At this time, the color of the solution changes from light blue to dark brown, indicating that the Cu NCs@PAA hydrogel composite material is successfully prepared.
[0055] (2) The Cu NCs@PAA hydrogel composite material obtained in step (1) is coated on the polished electrode surface, and after drying, an ECL intensity test is performed on it using an electroluminescence instrument.
[0056] Fig.11 Cu NCs@PAA hydrogel composites at 100 mmol L -1 The ECL stability graph of 10 consecutive scans in K2S2O8 solution shows that the prepared composite material exhibits excellent stability, and its relative standard deviation (RSD) is 3.1%. Embodiment 5
[0057] An electrochemiluminescent sensor based on PAA hydrogel for inducing aggregation of Cu NCs and a preparation method thereof, comprising the following steps: (1) Take 70 μL of AgNO3 (10 mmol L ‒1 ), 100 μL of freshly prepared ammonium persulfate (50 mmol L ‒1 ) and 120 μL of acrylic acid dispersed in 230 μL of ultrapure water can achieve ultra-fast gelation. Then, using PAA hydrogel as a template, copper nanoclusters were generated on it. First, 250 μL of CuSO4 (8 mmol L ‒1 ) solution, and after it is fully mixed, NaOH solution is added to adjust the pH to 12. At this time, the color of the solution gradually changes from colorless to light blue. After the solution is fully mixed, 100 μL of hydrazine hydrate solution is finally added. At this time, the color of the solution changes from light blue to dark brown, indicating that the Cu NCs@PAA hydrogel composite material is successfully prepared.
[0058] (2) The Cu NCs@PAA hydrogel composite material obtained in step (1) is coated on the polished electrode surface, and after drying, an ECL intensity test is performed on it using an electroluminescence instrument.
[0059] Fig.12 Cu NCs@PAA hydrogel composites at 100 mmol L -1 The ECL stability graph of 10 consecutive scans in K2S2O8 solution shows that the prepared composite material exhibits excellent stability, and its relative standard deviation (RSD) is 3.5%. Comparative Example 1
[0060] The preparation of Cu NCs includes the following steps: First, use a pipette to measure 580 μL of ultrapure water, then add 150 μL of CuSO4 (8 mmol L ‒1 ) solution, followed by adding NaOH solution to adjust the pH to 12. The color of the solution gradually changed from colorless to light blue. After the solution was fully mixed, 100 μL of hydrazine hydrate solution was added. The color of the solution changed from light blue to dark brown, indicating that the Cu NCs were successfully synthesized.
[0061] Fig.13 For Cu NCs at 100 mmol L -1 The relative standard deviation (RSD) of the ECL stability diagram after 10 consecutive scans in K2S2O8 solution was 3.9%. Comparative Example 2
[0062] The preparation of Ag NCs@PAA hydrogel composites includes the following steps: (1) Take 70 μL of AgNO3 (10 mmol L ‒1 ), 100 μL of freshly prepared ammonium persulfate (50 mmol L ‒1 ) and 120 μL of acrylic acid were dispersed in 230 μL of ultrapure water to achieve ultra-fast gelation. Then, NaOH solution was added to the PAA hydrogel to adjust the pH to 12. After the solution was fully mixed, 100 μL of hydrazine hydrate solution was added. After sufficient reaction, the Ag NCs@PAA hydrogel composite material was successfully prepared.
[0063] (2) The Ag NCs@PAA hydrogel composite material obtained in step (1) is coated on the polished electrode surface, and after drying, an ECL intensity test is performed on it using an electroluminescence instrument.
[0064] Fig.14 For Ag NCs@PAA hydrogel at 100 mmol L -1 The ECL stability diagram of 10 consecutive scans in K2S2O8 solution shows that its ECL emission is very low and very unstable.
[0065] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An aggregation-induced electrochemiluminescent composite material, characterized in that: The copper nanoclusters are confined in the three-dimensional structure of polyacrylic acid hydrogel, wherein the polyacrylic acid hydrogel is a polyacrylic acid initiator and Ag. + The hydrogel formed under the action of a cross-linking agent has a ratio of the copper nanoclusters to acrylic acid of 0.1-0.5 mol:30L.
2. The method for preparing the aggregation-induced electrochemiluminescent composite material according to claim 1, characterized in that: The steps include: Step a, accurately measuring silver nitrate solution, ammonium persulfate solution and acrylic acid, and fully dispersing them in ultrapure water; reacting at room temperature for 3 to 7 minutes to obtain polyacrylic acid hydrogel; wherein the volume ratio of silver nitrate solution, ammonium persulfate solution, acrylic acid and ultrapure water is 7:10:12:23; Step b, adding copper sulfate solution to the polyacrylic acid hydrogel and mixing thoroughly, adjusting the pH value of the system to alkaline; after the solution is fully mixed, adding hydrazine hydrate solution and reacting thoroughly to obtain the aggregation-induced electrochemiluminescent composite material.
3. The method for preparing the aggregation-induced electrochemiluminescent composite material according to claim 2, characterized in that: In step a, the concentration of the silver nitrate solution is 5 to 15 mmol L ‒1 The concentration of ammonium persulfate solution is 30~70mmol L ‒1 .
4. The method for preparing the aggregation-induced electrochemiluminescent composite material according to claim 2, characterized in that: In step b, the concentration of the copper sulfate solution is 5 to 15 mmol L ‒1 , the volume ratio of copper sulfate solution to acrylic acid is 5~25:
12.
5. The method for preparing the aggregation-induced electrochemiluminescence composite material according to claim 2, characterized in that: In step b, the pH is adjusted to 12.
6. An aggregation-induced electrochemiluminescence biosensor, characterized in that: The invention comprises a modified electrode obtained by modifying the aggregation-induced electrochemiluminescent composite material according to claim 1 on the surface of a conductive substrate.
7. The aggregation-induced electrochemiluminescence biosensor according to claim 6, characterized in that: It also includes a platinum wire electrode as a counter electrode, a silver / silver chloride electrode as a reference electrode, and a phosphate buffer solution containing 80-120 mM K2S2O8 with a pH of 7.4 as an electrolyte.
8. Use of the aggregation-induced electrochemiluminescence biosensor according to claim 6 or 7 in detecting folic acid, characterized in that: The ECL performance was detected by electrochemiluminescence; the applied scanning potential range was -2 to 0 V, the photomultiplier tube high voltage was 800 V, and the scanning rate was 100 mV / s.